Method of transformation of printed circuit boards regular interconnection into polygonal - Murov S. Yu. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2010)
The described method allows to automate the polygonal interconnection process, which is essential for powerful radio transmitters designing, and also for multi-layer printed circuit boards designing, when the reference layer includes several different circuits.